PUBLIC VALUE PORTAL ONE DATA PALAPA IN THE MEDIA TO SHARE DATA IN THE SCOPE OF MOJOKERTO REGENCY - Winantoro, Adistin Naidzira Prameswari; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to explain the implementation of the Palapa One Data Portal as an e-government-based public service innovation in Mojokerto Regency and how the portal realizes public value. This portal was developed to make it easier for the public to access data sourced from various local government agencies in a transparent and integrated manner. Method:. The method used is qualitative descriptive with data collection techniques through interviews and document analysis. The research informants included village apparatus and the community using the portal, while the analysis was conducted using the Public Value Strategic Triangle framework by Mark Moore and the Public Value Scorecard by Gomez & Meynhardt. Novelty; This research presents a novelty because it analyzes the implementation of the Palapa One Data Portal in Mojokerto Regency with a Public Value perspective, using Mark Moore's theory and Gomez & Meynhardt's Public Value Scorecard. This study differs from previous studies that have generally focused on large cities or the technical aspects of e-government, as it emphasizes on how regional data portals can create public value across aspects (economic, social, political, educational, and ecological) as well as operational challenges in data updates.